Identifikasi Alga Merah di Provinsi Gorontalo - Rully Tuiyo (The NIKe Journal, 2014)
Coastal areas and the seas on the northern and southern parts of Gorontalo Province are big natural and fisheries resources. Some that has potentials to be developed are the cultivation of sea algae. The aim of this research was to identifity all the red algae found in Gorontalo Province. Method of survey is to explore and identify the algae without area unit and transek. The algae are washed clean and photographed with digital camera for further identification. Red algae that was found on Nort and South coasts of Gororntalo Province is the species Halymenia durvillaei distributed in Gentuma, Ponelo, Molotabu and Huangobotu Villages. Keywords: identification, red algae, Gorontalo Province